23‐3: A Histogram based Method for Dynamic Range Expansion. Issue 1 (May 2017) - Han, Yan; Michelini, Pablo Navarrete; Hanwen, Liu; Duan, Ran
Abstract : A method for Dynamic Range expansion is presented with its FPGA solution. This can help us converting a Low Dynamic Range image to a High Dynamic Range one. So that we can use more available brightness levels of display panel and see unseen details of images.